The Factors Behind the Failure of the Fatimids in Dominating the Northern Regions of Sham"Syria" (4th and 5th Centuries AH) - Azam Rahmatabady (پژوهش های تاریخی)
After defeating the Aghlabids and establishing a state in Ifriqiya, the Fatimids conquered Egypt and launched a military campaign to the Levant to achieve their goals. The southern and central regions of the Levant fell to them with little resistance, but the northern regions of the Levant resisted Fatimid domination. This resistance caused the Fatimids to be halted in Aleppo and prevented them from advancing toward Iraq, thwarting their ambition to expand their influence in the eastern parts of the Islamic world. This research, conducted using a descriptive-analytical method, examines the factors behind the Fatimids’ weakness in the northern Levant. The findings of the study show that multiple factors contributed to this resistance, including the strategic position and economic independence of Aleppo, the significant distance between Aleppo and Cairo, the difficulties in sending forces by the Fatimids, Byzantine interference in the political and military affairs of northern Sham, the independence-seeking policies of the Hamdanid and Banu Mardas rulers, the administrative and military weaknesses of the Fatimid state in Sham, the exploitation of these weaknesses by the rulers of Aleppo, the religious conflicts between the Fatimids and the inhabitants of Sham, the Shiite Imams in the region, and ethnic prejudices. These factors made Aleppo an impregnable stronghold during the Fatimid rule.